C–H Trifluoromethylthiolation of aldehyde hydrazones - Victor Levet; Balu Ramesh; Congyang Wang; Tatiana Besset (Beilstein Journal of Organic Chemistry)
The selective C–H trifluoromethylthiolation of aldehyde hydrazones afforded interesting fluorinated building blocks, which could be used as a synthetic platform. Starting from readily available (hetero)aromatic and aliphatic hydrazones, the formation of a C–SCF3 bond was achieved under oxidative and mild reaction conditions in the presence of the readily available AgSCF3 salt via a one-pot sequential process (28 examples, up to 91% yield). Mechanistic investigations revealed that AgSCF3 was the active species in the transformation.